Kyrgyzstan land rights: Quick guide to resolving disputes and securing ownership - Bainazarov, Iskander (2024)
This set of briefs was produced as an easy-to-use guide to address the challenges surrounding land rights in Kyrgyzstan based on the Kyrgyz land, civil and family codes. Its primary goal is to offer Kyrgyz citizens a clear understanding of their rights, legal processes, and practical steps related to land ownership. It covers seven scenarios of land ownership for women and men, and disputes common in Kyrgyzstan, ranging from resolving marital property disputes to addressing unauthorized land expansions and combating squatting on agricultural lands.